Body composition of Slovenian artistic and rhythmic gymnasts - Istenic, N.; Samardzija Pavletic, M. (International Scientific Congress Slovenian Gymnastics Federation, 2018)
Rhythmic and artistic gymnastics are both aesthetically judged sports where body weight and body composition are important performance variables. Since modulating body composition is an often-involved part of those disciplines, objective screenings are necessary prior and during those interventions to assess the progress and prevent possible health risks and decrease in performance. The goal of our study was to define the mean values of anthropometric variables among perspective Slovenian artistic and rhythmic gymnasts, to compare those values to the ranges established in literature and to point out the importance of healthy body composition modulation techniques in aesthetic sports such as artistic and rhythmic gymnastics. The results show that there are differences in body composition between the disciplines, with RG being under suggested healthy ranges. The focus of the study was on collecting the data on body composition, but we would also like to point out the possible health risks in weight-sensitive sports and suggest some guidelines for further research in this field.